Is coral richness related to community resistance to and recovery from disturbance? - Zhang, Stacy Y.; Speare, Kelly E.; Long, Zachary T.; McKeever, Kimberly A.; Gyoerkoe, Megan; Ramus, Aaron P.; Mohorn, Zach; Akins, Kelsey L.; Hambridge, Sarah M.; Graham, Nicholas A.J.; Nash, Kirsty L.; Selig, Elizabeth R.; et al. (PeerJ, 2014)
More diverse communities are thought to be more stable—the diversity–stability hypothesis—due to increased resistance to and recovery from disturbances. For example, high diversity can make the presence of resilient or fast growing species and key facilitations among species more likely. How natural, geographic biodiversity patterns and changes in biodiversity due to human activities mediate community-level disturbance dynamics is largely unknown, especially in diverse systems. For example, few studies have explored the role of diversity in tropical marine communities, especially at large scales. We tested the diversity–stability hypothesis by asking whether coral richness is related to resistance to and recovery from disturbances including storms, predator outbreaks, and coral bleaching on tropical coral reefs. We synthesized the results of 41 field studies conducted on 82 reefs, documenting changes in coral cover due to disturbance, across a global gradient of coral richness. Our results indicate that coral reefs in more species-rich regions were marginally less resistant to disturbance and did not recover more quickly. Coral community resistance was also highly dependent on pre-disturbance coral cover, probably due in part to the sensitivity of fast-growing and often dominant plating acroporid corals to disturbance. Our results suggest that coral communities in biodiverse regions, such as the western Pacific, may not be more resistant and resilient to natural and anthropogenic disturbances. Further analyses controlling for disturbance intensity and other drivers of coral loss and recovery could improve our understanding of the influence of diversity on community stability in coral reef ecosystems.
Keywords: Biodiveristy; Resilience; Stability; Coral reef; Disturbance; Recovery; Resistance; Community ecology